Mg line formation in late-type stellar atmospheres: I. The model atom - Osorio, Y.; Barklem, P. S.; Lind, K.; Belyaev, A. K.; Spielfiedel, A.; Guitou, M.; Feautrier, N. (Astronomy and astrophysics (Berlin), 2015)
Magnesium is an element of significant astrophysical importance, often traced in late-type stars using lines of neutral magnesium, which is expected to be subject to departures from local thermodynamic equilibrium (LTE). In this paper we build and test a Mg model atom for spectral line formation in late-type stars with new or recent inelastic collision data and no associated free parameters. We aim to reduce these uncertainties and thereby improve the accuracy of Mg non-LTE modeling in late-type stars. For the low-lying states of Mg [subI], electron collision data were calculated using the R-matrix method. Our results emphasize the need for accurate data of Mg collisions with both electrons and H atoms for precise non-LTE predictions of stellar spectra, but demonstrate that such data can be calculated and that ab initio non-LTE modeling without resort to free parameters is possible. Grids of departure coefficients and abundance corrections for a range of stellar parameters are planned for a forthcoming paper.